PROCESSES AFFECTING SUSTAINABLE USE OF AGRICULTURAL LAND IN KOSOVO - Ramadani, Ibrahim; Bytyqi, Valbon (Quaestiones Geographicae, 2018)
Agricultural land is facing challenges due to different human activities. Accelerated urbanisation along with explosive economic growth has further worsened the shortage of agricultural land over the last two decades. Kosovo, a country with small areas suitable for agriculture is meeting challenges due to unplanned settlement extension, coal surface mining, parcelisation of properties, etc. This paper consists in an analysis of the agricultural land fund in Kosovo, in quality, production potential and food security for the population, but also the challenges facing Kosovo with this strategic resource. The article analyses three main factors that have made the biggest changes in agricultural land in Kosovo: the effects of settlement extension, coal surface mining and parcelisation in reducing the soil fund. Some of the effects have triggered significant socio-economic processes that have changed the rural environment. Other important risks of agricultural land in Kosovo are: pollution, landfills, frequent floods, etc.